Effect of delayed elective surgeries during COVID-19 pandemic - Siddiqui, Mohammad S.; Alrumayh, Shouq S.; Alothman, Nada T.; Al Rheman, Saad A.; Alsalman, Ali H.; Alzbedi, Hassan H.; Nafa, Fatemh A.; Alotaibi, Mutaib N.; Almadan, Ali F.; Ahmed, Rahaf S.; Siddiqui, Moaz M. (International Journal Of Community Medicine And Public Health, 2021)
The field of surgery has been greatly affected during the pandemic due to the shift of resources to manage the huge numbers of COVID-19 cases. In this study, we aim to review the effect of the COVID-19 pandemic and lockdown measures on elective surgeries and the subsequent complications, in addition to the previously announced preparations and precautions for performing surgeries whenever indicated. Preparations include the availability of resources and performing each surgery in separate rooms away from other wards within the hospital to prevent any possibility of nosocomial infections. Moreover, limiting the number of individuals within the operation room and wearing personal protective equipment should be done. Limiting hospital visits and reducing in-hospital stays is also recommended. Regarding cancer operations, malignant tumors that were indicated for surgeries cannot be postponed. However, other non-malignant ones can be delayed depending on the pathologist's perspective and the symptomatology of the tumor. Besides, other surgeries like plastic and reconstructive ones can be re-scheduled. Additionally, most surgeries like urologic, orthopedic, and neurological operations can be delayed unless they are associated with a life-threatening lesion that can only be healed by surgical interference. On the other hand, palliative surgeries aiming to manage obstructions of the gastrointestinal tract cannot be delayed.